INNOVATION AND TRANSFORMATION OF PRODUCTION COST CONTROL IN IMPROVING THE QUALITY OF AGRICULTURE RESOURCES AS AN ACCELERATION SOLUTION TO SUPPORT BUSINESS SECTOR AGRICULTURE DURING THE COVID 19 PERIOD IN INDONESIA - IGP Ratih Andaningsih Gusti (Bajang Institute, 2021)
ABSTRACT This research analyses development of innovation agroecology and innovation socio economy business conditions in Indonesia. The agriculture needs agriculture controlling report of cost production and tools and machinery support and solution with certain characteristics. The transformation business practically development of innovation business industry of agriculture materials is one of the efforts to improve competence and skill. The purpose of this study is to find out solutions practice in agriculture mechanicsm in business sector industry,administration agriculture aspects and management business agriculture area in controlling of cost production. This research has an impact on post pandemic Covid 19 in Indonesia. The limitation of this research is the increasing innovation and transformation agriculture mechanicsm and solution in accelerated and supporting busness industry of agriculture sector in Pandemic Covid 19 in Indonesia.The Contribution of This research are that business industry of agriculture are able to maintain skill and knowledge of controlling cost production and innovation and transformation technology of agricultur business sector. Keywords: Inovation,Transformation,Controlling,Business Industry,Agriculture,CostProduction.